Pre-filters in-transit malware packets detection in the network - Ban Mohammed Khammas; Ismahani Ismail; M. N. Marsono (Universitas Ahmad Dahlan, 2019)
Conventional malware detection systems cannot detect most of the new malware in the network without the availability of their signatures. In order to solve this problem, this paper proposes a technique to detect both metamorphic (mutated malware) and general (non-mutated) malware in the network using a combination of known malware sub-signature and machine learning classification. This network-based malware detection is achieved through a middle path for efficient processing of non-malware packets. The proposed technique has been tested and verified using multiple data sets (metamorphic malware, non-mutated malware, and UTM real traffic), this technique can detect most of malware packets in the network-based before they reached the host better than the previous works which detect malware in host-based. Experimental results showed that the proposed technique can speed up the transmission of more than 98% normal packets without sending them to the slow path, and more than 97% of malware packets are detected and dropped in the middle path. Furthermore, more than 75% of metamorphic malware packets in the test dataset could be detected. The proposed technique is 37 times faster than existing technique.